Chemical profile and evaluation of antioxidant activity of methanolic extracts from the leaves of Spondias bahiensis P. Cardoso, Spondias tuberosa Arruda, Spondias mombin L. (Research, Society and Development, 2025)
Plants contain chemical compounds that are used as raw materials for drug development, as they perform biological activities. Pharmacological studies with Spondias species demonstrate the presence of these constituents. This study aims to perform the chemical profile and analyze the antioxidant and toxicological activity of methanolic extracts from the leaves of Spondias bahiensis, Spondias tuberosa, and Spondias mombin. The phytochemical screening evaluated the presence of 12 classes of secondary metabolites; antioxidant activity was based on the scavenging capacity of the free radical DPPH (2-diphenyl-1-picrylhydrazyl); toxicity was assessed against Artemia salina. Phenolic compounds were identified in the extracts. The antioxidant test revealed better activity of the methanolic extract of S. mombin compared to the methanolic extracts of S. tuberosa, S. bahiensis, and ascorbic acid. Regarding toxicity, the extracts were considered toxic at high concentrations. Thus, the species present promising constituents for use in research with natural products.